The Impact of Training, Environment, and Motivation on Performance - Hilman Eka Putra; Fathorrahman Fathorrahman; Murtianingsih Murtianingsih (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The management of regional property is a crucial aspect of good governance, requiring competent human resources. The quality of human resources is measured by the performance produced, where quality HR has the potential to achieve optimal performance. This study aims to analyze the extent of the influence of training, work environment, and work motivation on the performance of property management staff in the government of Sabang City. The population of this study consists of all property management staff in the government of Sabang City in May 2025, with a sample of 34 respondents using a saturated sampling technique, and data collection was conducted using a 5-point Likert scale questionnaire. This study also employed multiple linear regression analysis using SPSS. The results indicate that: 1) Training does not significantly influence the performance of property management staff at local government agencies of Sabang, 2) Work environment does not significantly influence the performance of property management staff at the City Government of Sabang, 3) Work motivation significantly influences the performance of property management staff at the City Government of Sabang.